2015
DOI: 10.1371/journal.pone.0142239
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Vitamin D Status with Glucose Tolerance and Caesarean Section in a Multi-Ethnic Asian Cohort: The Growing Up in Singapore Towards Healthy Outcomes Study

Abstract: ObjectiveEpidemiological studies relating maternal 25-hydroxyvitamin D (25OHD) with gestational diabetes mellitus (GDM) and mode of delivery have shown controversial results. We examined if maternal 25OHD status was associated with plasma glucose concentrations, risks of GDM and caesarean section in the Growing Up in Singapore Towards healthy Outcomes (GUSTO) study.MethodsPlasma 25OHD concentrations, fasting glucose (FG) and 2-hour postprandial glucose (2HPPG) concentrations were measured in 940 women from a S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 47 publications
2
42
2
1
Order By: Relevance
“…Also, Loy et al did not observe a relationship between 25(OH)D inefficiency/deficiency and GDM [47]. In the B.A.B.Y.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Loy et al did not observe a relationship between 25(OH)D inefficiency/deficiency and GDM [47]. In the B.A.B.Y.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the association between dietary factors and the risk of GDM have just emerged over the last decade. There is evidence suggests that plasma vitamin D and vitamin C concentrations in early pregnancy and dietary fat intake during pregnancy may be implicated in the aetiology of GDM [6,14]. However, it is worth noting that the number of GDM cases in the majority of these studies is rather low in general and extremely limited among the non-Caucasian population.…”
mentioning
confidence: 99%
“…The reported figure of Hypo-VD goes in hand with Loy et al [33] who reported VD inadequacy rate of 41.3%, and Al-Shaikh et al [34] who reported VD deficiency in 86.4% of pregnant females in Riyadh and GDM was the commonest complication detected in 11.1%. Moreover, Karras et al [35] out of literature systemic review found the prevalence of VD insufficiency among pregnant Greece women ranged from 9.3 to 41.4%, whereas that of VD deficiency from 22.7 to 90.3%.…”
Section: Discussionmentioning
confidence: 96%